Difficult heritage negotiating the Nazi past in Nuremberg and beyond - Macdonald, Sharon Jeannette 1961- (Routledge, 2009)
How does a city and a nation deal with a legacy of perpetrating atrocity? How are contemporary identities negotiated and shaped in the face of concrete reminders of a past that most wish they did not have? Focusing on the case of Nuremberg, this text explores these questions and their implications.
Literaturverz. S. 212-224; Rez.: MVGN 99 (2012), S. 342 - 347 (Hartmut Frommer)
Keywords: Geschichte 1900-2000; Architektur; Geschichte; Psychologie; Postwar reconstruction -- Germany -- Nuremberg; National socialism -- Psychological aspects; Collective memory -- Germany -- Nuremberg; Cultural property -- Germany -- Nuremberg; Kollektives Gedächtnis; Nationalsozialismus; Vergangenheitsbewältigung; Deutschland; Nuremberg (Germany) -- Buildings, structures, etc; Nuremberg (Germany) -- History -- 20th century; Nürnberg